PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI DESA KEDEWATAN KABUPATEN GIANYAR - Sutarsana, I Gede Andre (Kerta Dyatmika, 2023)
The Complete Systematic Land Registration (PTSL) is a national program aimed at conducting the initial land registration simultaneously for all land registration objects within a village or sub-district across the Republic of Indonesia. One of the target areas for the implementation of this program is Kedewatan Village in Gianyar Regency, Bali. This village was selected due to its low land certification rate, which remains below 65% of the total area of 435 hectares, divided into six local community units (banjar). This research aims to examine the implementation of PTSL in Kedewatan Village and to identify the obstacles encountered during its execution. The research employs an empirical legal method with a descriptive approach, aiming to depict the situation as it occurs in practice. The findings indicate that the implementation of PTSL in Kedewatan Village proceeded effectively and in accordance with the prescribed phases, supported by continuous updates of land data within the stipulated timeframe. Nevertheless, several challenges remain, both technical and juridical in nature. In response, the National Land Agency (BPN) of Gianyar Regency has undertaken various measures, including encouraging active participation from local communities and village officials, conducting public outreach on the importance of PTSL, and enhancing coordination with local government authorities. In conclusion, while the implementation of PTSL in Kedewatan Village has shown positive results, stronger collaboration among stakeholders is essential to overcome the existing barriers.